Peningkatan Kemampuan Digital Branding Usaha Mikro Kecil Dan Menengah (UMKM) Melalui Literasi Digital Berbasis Artificial Intelligence (AI) - Sari, Nimas Ratna (TERANG, 2024)
Digitalization of MSMEs is planned to increase MSME opportunities and develop their businesses, but not all MSMEs can easily switch to digital platforms. Several MSMEs have entered digital platforms, making competition even tighter. Each MSME must have strategies and advantages so that their products do not lose out in the competition. MSMEs operating in the culinary sector also face challenges for business continuity. One way to increase the value of food products is with certain certifications specifically aimed at food products, such as halal certification. Food products that have a halal certificate will increase consumer confidence in buying these products. Therefore, halal certification is an asset that can be used to develop a business image. However, developing a business image experiences challenges because the majority of MSMEs in Indonesia have a limited workforce to optimize the business they run. This means that image development, especially on digital media such as social media, is often sidelined due to limited ability and time. Artificial intelligence applications, especially generative AI, are one solution to simplify and shorten work time so that MSME managers can build a digital image of their business more easily.